SYSTEMATIC LITERATURE REVIEW: MODEL PEMBELAJARAN PROJECT BASED LEARNING (PJBL) TERHADAP SKILL YANG DIKEMBANGKAN DALAM TINGKATAN SATUAN PENDIDIKAN - Kurniawan, Andri; Yuhana , Yuyu; Fathurrohman, Maman (Jurnal Tinta, 2024)
The purpose of this study is to look at the competencies that can be formed through the use of project-based learning (PjBL) learning models. This study uses the Systematic Literature Review (SLR) method. This study analyzes search results from the Scopus, Erics, and Google Scholar databases, with a span of the last 10 years. Based on the search results, 100 relevant articles were obtained which were then filtered based on the inclusion criteria and 41 articles were used as the primary study. Each article in the data, then analyzed based on the capabilities developed from research results. The results of the review analysis of this article can be drawn conclusions and findings that the learning model (PjBL) has a good impact on improving hard skills and soft skills in learning mathematics both at the elementary, junior high and high school / vocational levels. At the elementary level, PjBL is able to improve critical thinking skills and increase motivation to learn, at the SMP level PjBL is able to improve creative thinking skills and increase students' learning motivation, and at the high school level PjBL is able to improve creative thinking skills and increase students' interest in learning.